Criminal Justice Response to Victim Harm in the United States, 1981 - Hernon, Jolene C. ([Verlag nicht ermittelbar], 1989)
This data collection examines the ways in which victim harm affects decisions regarding arrest, prosecution, and sentencing, and the impact of these decisions on the victim's perception of the criminal justice system. Five types of offenses were studied: homicide, sexual assault, burglary, robbery, and aggravated assault. The victim file contains information on personal characteristics, results of victimization, involvement in case processing, use of victim assistance service, satisfaction with case outcomes, and opinions about the court system. The police file and the prosecutor file variables cover personal background, screening decisions on scenario cases, communication with victims, and opinions about the role of victims in the criminal justice system. The prosecutor file also includes sentencing recommendations on the scenarios. Data in the judge file cover personal background, sentencing recommendations on the scenario cases, communications with victims, sources of information regarding victim harm, and opinions about the role of victims in the criminal justice system.